Relationship between vaccination and atopy - Jagelavičienė, Agnė; Usonis, Vytautas (Acta medica Lituanica, 2014)
Background. The rising prevalence of atopic diseases during last decades brings concern for the “Western life-style” countries. Although there is general consensus on the importance of the genetic predisposition for atopic disorders (asthma, allergic rhinitis, atopic dermatitis), only changes in environmental factors can explain the rise of allergic diseases during the last forty years. Vaccinations in infancy have been incriminated as an additional risk factor for development of atopic diseases. A potential relationship between vaccination and atopy could be analysed by two directions: either by activation of the Th2 network in the vaccine-specific memory response, or exposition to (attenuated or inactivated) pathogens or their components at a very young age of vaccinated children and possible promotion of Th1 proliferation. Materials and methods. The major electronic databases (Medline, Cochrane Library) were searched using key words: vaccination, atopy, relationship and children. Recent studies analysing a relationship between atopic disorders and vaccination in infancy were reviewed. Moreover, possible mechanisms of immune response to vaccines in atopic children were analysed. Results. Available evidence is rather convincing that the current regular childhood vaccination does not increase the risk of atopic disorders. Large epidemiological, prospective, cohort and multi-central studies all over the world published in last 10 years with quite large proportions of unvaccinated children included showed that vaccination in infancy was not related to development of atopic conditions starting from the first year of life up to the middle age. Even conversely, some studies detected that vaccinated children had a moderately reduced rate of atopic diseases. It was also denoted that atopy could be suppressed due to high vaccination coverage. Conclusions. Allergic or atopic children just like non-atopic children require routine immunization to be protected from serious life and health threatening viral and bacterial infections. The risks of infection by vaccine avoidance outweigh by far the possible minimal risks of immunization, moreover, anti-infectious treatment or natural infection (like pertussis) per se could be potential triggers of atopic disorders.